Emotional Intelligence and Self-Efficacy as Determinants of ICT Competence among Professional Counselors in Kwara State, Nigeria - Lasisi, Adekola Kamil; Makinde, Semiu Olawale (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study investigated emotional Intelligence and self-efficacy as determinants of ICT Competence among Professional Counsellors in Kwara State, Nigeria. A descriptive research design of survey type was used. Two null hypotheses were formulated and tested to ascertain the relationship between independent variables and dependent variables. Three instruments: The emotional intelligence scale with a reliability index of 0.68; the General Self-Efficacy Scale with a 0.74 reliability coefficient; and the ICT skill scale with a 0.83 reliability coefficient were adapted for the study. The target population were all 230 professional counsellors in Kwara State, Nigeria. A Purposive sampling technique was used to select 120 professional counsellors in Kwara State as respondents. Data collected was analyzed using inferential statistical tools of Pearson Product Moment Correlation Coefficient (PPMC) to test the relationship between variables of the study at a 0.05 level of significance. Findings show that there was a significant positive relationship between emotional intelligence, self-efficacy and ICT competence among professional counsellors in Kwara State. The study concluded that emotional intelligence and self-efficacy are strong determinants of ICT competency but self-efficacy is stronger among professional counsellors in Kwara State, Nigeria. Hence, it was recommended among others that the university management should equip the counselling units with modern ICT tools like radio recording machines, and computers with Internet facilities to ensure professional counsellors’ high emotional intelligence and maximum self-efficacy which could facilitate effective integration of ICT for the provision of counselling services to students and staff.